Kuwaiti plants : distribution, traditional medicine, pytochemistry, pharmacology and economic value - Middleditch, Brian S. (Studies in plant science, 1991)
The people of Kuwait have in the past depended almost entirely on the sea trade giving its boat builders and sailors a good reputation. Plants in Kuwait were valued only as forage and fodder and for subsistence-level farming. Although oil was discovered in 1938, production of oil did not commence until after the second world war. Coupled with recent unrest in the region, extensive damage has been caused to many of Kuwait's plants and a good review of information on them became necessary. The book contains information on all of the dicothyledonous plants (except the Compositae) known to grow in Kuwait. Many of the species of plants are reviewed in their traditional uses in Kuwait and elsewhere. Extensive searches of scientific literature were carried out on phytochemistry, pharmacology, contemporary economic value of the plants. Brief notes are also provided on the utility of related species. The distribution of the 118 species covered is illustrated on maps of Kuwait and the Middle East.